Relevance of Ambedkar today (New Delhi Pentagon, 2017)
Ambedkar was a passionate nation builder. He gave voice to all deprived sections of the society. His views on diverse national issues were pragmatic and converge with the challenges even during the era of globalization. Ambedkar was aware about the incoming turbulence of nation building therefore has suggested means to achieve it. He laid the foundation of human rights in contemporary India through providing legal protection to vulnerable sections. India is passing through an extremely critical phase today. Ambedkar has suggested structural mechanism to cope up with the situation. Due to parochial politics, Ambedkar became an object to score narrow political dividends. Modi government has however successfully change the construct of this debate and declared him as one of the top nation builders. This work has tried to view Ambedkar in a holistic manner. The papers included in this book are dealing with all those pertinent issues.
Keywords: Political Science; Political Ideology; Dr. Ambedkar